Effect of incorporating tributyrin and tricaproin in milk replacer on the hepatic metabolome of calves - Í.R.R. Castro; M.H. Ghaffari; L.N. Leal; H. Sauerwein; M.I. Marcondes; G.B.C. Leite; J.N. Wilms (Journal of Dairy Science)
ABSTRACT: This study investigated the effects of including a spray-dried fat concentrate containing tributyrin (TB) and tricaproin (TC) in milk replacer (MR) on the liver metabolome of dairy calves. Forty-five male dairy calves (46.1 ± 4.6 kg BW; 2.1 ± 0.63 d of age; mean ± SD) were blocked in order of arrival at the research facility. Within each block, calves were randomly assigned to 3 MR treatments (n = 15 per group): (1) an MR containing milk fat serving as biological reference for fat composition (MF), (2) a control MR (CON) containing a blend of vegetable fats, and (3) an MR (TRI) containing the same mixture of vegetable fats as CON, into which TB and TC were incorporated. All MR were isoenergetic with 36% lactose, 27% fat, and 24% protein on a DM basis. Calves were housed individually and received MR (13.5% solids) via nipple buckets twice daily at 0630 and 1730 h. Daily MR allowance was 6.0 L from d 1 to 5, 7.0 L/d from d 6 to 9, and 8.0 L/d from d 10 to 35. Calves had ad libitum access to water and chopped straw but no starter feed was fed. On d 35 after arrival, calves were euthanized and liver tissue samples were collected and analyzed using a targeted metabolomics approach. Liquid chromatography and flow injection with electrospray ionization triple quadrupole mass spectrometry using an MxP Quant 500 kit was used. Distinct metabolic profiles emerged, with principal component analysis indicating differences between calves fed MF and those on other treatments, collectively accounting for almost 50% of the total variation. Partial least squares discriminant analysis confirmed significant differences between the liver metabolomes of calves fed MF and other treatments. Volcano plot analysis showed that compared with calves fed CON, 51 metabolites were higher in calves fed MF, including 34 phosphatidylcholines, 8 sphingomyelins, 3 lysophosphatidylcholines, 1 ceramide, 3 hexosylceramides, eicosapentaenoic acid (EPA) and glycochenodeoxycholic acid (GUDCA), while 8 metabolites were lower, including 2 phosphatidylcholines, 1 sphingomyelin (SM C22:3), 1 diacylglycerol (DG 16:0_18:2), 1 lysophosphatidylcholine (lysoPC a C18:2), 2 nitrogen-containing compounds (putrescine and serine), and C5 acylcarnitine. In addition, when comparing calves fed MF to calves fed TRI, 51 metabolites were higher in calves fed MF, including 37 phosphatidylcholines, 8 sphingomyelins, 4 lysophosphatidylcholines, 3 ceramides, 3 hexosylceramides, EPA and GUDCA, while 7 metabolites were lower, including 2 phosphatidylcholines, 1 sphingomyelin (SM C22:3), 1 diacylglycerol (DG 16:0_18:2), 1 lysophosphatidylcholine (lysoPC a C18:2), putrescine and valerylcarnitine (C5). Importantly, no significant differences in metabolites were found between calves fed CON and TRI, suggesting that TB and TC in MR had no effect on the liver metabolome. These results demonstrate that differences in MR fat composition between milk fat (MF) and vegetable fats (CON and TRI) significantly modulate the liver metabolome of calves and underscore the importance of addressing fat composition in MR formulations to optimize metabolic outcomes.